Comparison of Patients Satisfaction Before and During Covid 19 Strike Pandemic at RSUD Mampang Prapatan Jakarta - Kelvin Evaline Riupassa (Jurnal Admmirasi, 2021)
In the era of Covid-19 pandemic, health services have been forced to keep the services level the same as before pandemic. Hospitals as a public service regularly make surveys about patient satisfaction. Regulation released by the Minister of Administrative Reform of Bureaucratic Reform No. 14 of 2017 ordered all public services to analyze 9 elements that influence customer satisfaction. This study aims to make comparison of patient’s satisfaction before and during Covid-19 strike pandemic at RSUD Mampang Prapatan Jakarta in outpatient and inpatient services areas. The research method used is a questionnaire method with a quantitative approach using Google Form questionnaire for patient satisfaction at RSUD Mampang Prapatan Jakarta before Covid-19 and during Covid-19. This type of research is classified as a descriptive study with quantitative approaches. There was a significant difference in patient satisfaction level between before and during Covid-19 in RSUD Mampang Prapatan. (p value <0.001). Hopefully, Covid-19 Pandemic will not become a burden to hospitals for giving excellence services. Another research needs to be done involving more samples from hospitals in higher level/class.